Philosophical approaches in modern economics - Gerashchenko Igor Germanovich (Studia Humanitatis, 2024)
The paper considers main philosophical and methodological approaches in modern economic science. The author singles out postpositivist, analytical, neopragmatic, historical, dialectical-materialistic, pluralistic, eclectic, synergetic, postmodernist, game and relativistic methodological programmes. Their competition and complementarity are shown. The epistemological crisis in modern economic science is associated with the transition from classical economic theory to post-classical economic theory.